China’s Implementation of Panda Diplomacy in Indonesia: A Review of Constructivist Perspectives - Darmawan, Arif; Desfarika Putri, Reza (Department of International Relations Universitas Pertamina, 2021)
Bilateral relations between China and Indonesia have increased in recent years. Indonesia considers as a strategic partner of China in Southeast Asia. The application of Panda Diplomacy is proof that China considers Indonesia as a friendly country that has a significant meaning. Through the application of Panda Diplomacy, China strives to show a face that is friendly and does not pose a threat to other countries. In this article, we will discuss how the implementation of Panda Diplomacy by China in strengthening bilateral relations between China and Indonesia which will analyze through a constructivist perspective. This perspective views that the performance of Panda Diplomacy is a diplomacy tool and a symbol of friendship to shape a better Chinese image and identity. Here Constructivists see that Panda Diplomacy is a form of symbolic interaction. In carrying out panda diplomacy, indeed, China Government has thought of any strategies that can help in smoothing their national interests. So, Constructivists see this as an ideational focus on intersubjective beliefs as ideas, conceptions, and assumptions. However, there are other interests that China wants to achieve through a close relationship with Indonesia.